The Interaction of HLA-C1/KIR2DL2/L3 Promoted KIR2DL2/L3 Single-Positive/NKG2C-Positive Natural Killer Cell Reconstitution, Raising the Incidence of aGVHD after Hematopoietic Stem Cell Transplantation - Zuo, Wei; Yu, Xing-Xing; Liu, Xue-Fei; Chang, Ying-Jun; Wang, Yu; Zhang, Xiao-Hui; Xu, Lan-Ping; Liu, Kai-Yan; Zhao, Xiao-Su; Huang, Xiao-Jun; Zhao, Xiang-Yu (Frontiers in Immunology, 2022)
Natural killer (NK) cell education plays a vital role in leukaemia control and infection prevention after hematopoietic stem cell transplantation (HSCT). NK cell education is affected by the interactions of HLA-I/ killer immunoglobulin receptor (KIR). However, the various effects of different HLA-I/KIR interactions on NKG2C+ NK cell education are still controversial and unclear. In this study, we prospectively studied 128 patients with malignant haematologic disease who underwent HSCT. KIR2DL2/L3 single-positive/NKG2C+ cells were significantly expanded as NKG2C+ NK cells compared with KIR2DL1 or KIR3DL1 single-positive/NKG2C+ cells when donors and recipients were both HLA-C1/C1 or HLA-C1C1BW4 (P<0.05), with higher NKp30 expression (P<0.05). Moreover, KIR2DL2/L3 single-positive NK cells exhibited stronger expansion of NKG2C+ NK cells than conventional CD56dimNKG2C- NK cells (P<0.05). Additionally, the frequencies of KIR2DL2/L3 single-positive/NKG2C+ NK cells were correlated with the proportion of NKG2C+ NK cells among NK cells on Days 90 (P=0.0406). In conclusion, the interaction of KIR2DL2/L3 and HLA-C1 probably plays a dominant role in NKG2C+ NK cell reconstitution after HSCT, enhancing the expansion of NKG2C+ NK cells.